Evaluation of a new assay for nontuberculous mycobacteria species identification in diagnostic material and cultures. (September 2021) - Smirnova, Tatiana; Ustinova, Vera; Andreevskaya, Sofya; Larionova, Elena; Kiseleva, Ekaterina; Chernousova, Larisa; Varlamov, Dmitry; Sochivko, Dmitry; Ergeshov, Atadzhan
Abstract: The purpose of the present study was to evaluate a real-time PCR system for 12 nontuberculous mycobacteria (NTM) species identification developed by Central Tuberculosis Research Institute (CTRI; Moscow, Russia) in cooperation with Syntol LLC (Moscow, Russia). NTM cultures (210 strains, 19 species), Mycobacterium tuberculosis complex (MTBC) cultures (21 strains, 2 species), non-mycobacterial microorganisms (18 strains, 13 species) were used for the first stage of the assay evaluation. Clinical samples (sputum, N = 973) positive for smear microscopy and MTBC/NTM DNA by a PCR-based screening assay collected from 819 patients were used for specificity and sensitivity evaluation. Sensitivity for determining the NTM species directly from diagnostic material was 99.71%, with the specificity of 100%. The sensitivity and specificity for NTM species identification in cultures was 99.67% and 100%, respectively. Both sensitivity and specificity for determining MTBC in cultures was 100%. Highlights: The Real-Time PCR assay identifies 12 NTM species and allows to identify other NTM species as members of NTM group The assay differentiates between NTM and MTBC The assay allows to use both cultures and diagnostic material for the species identification